K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 2 2017

TH1: x<1/4 

=>2|x-3|-|4x-1|=2(3-x)-(1-4x)=6-2x-1+4x=5+2x

TH2: \(\frac{1}{4}\le x\le3\)

=>2|x-3|-|4x-1|=2(3-x)-(4x-1)=6-2x-4x+1=7-6x

TH3: x>3

=>2|x-3|-|4x-1|=2(x-3)-(4x-1)=2x-6-4x+1=-2x-5

HQ
Hà Quang Minh
Giáo viên
19 tháng 9 2023

a) 2x(x+3) – 3x2(x+2) + x(3x2 + 4x – 6)

= (2x . x + 2x . 3) – (3x2 . x + 3x2 . 2) + (x . 3x2 + x . 4x – x . 6)

= 2x2 + 6x – (3x3 + 6x2) + (3x3 + 4x2 - 6x)

= 2x2 + 6x – 3x3 – 6x2 + 3x3 + 4x2 - 6x

= (– 3x3 + 3x3 ) + (2x2  - 6x2 + 4x2 ) + (6x – 6x)

= 0 + 0 + 0

= 0

b) 3x(2x2 – x) – 2x2(3x+1) + 5(x2 – 1)

= [3x . 2x2 + 3x . (-x)] – (2x2 . 3x + 2x2 . 1) + [5x2 + 5 . (-1)]

= 6x3 – 3x2 – (6x3 +2x2) + 5x2 – 5

= 6x3 – 3x2 – 6x3 - 2x2 + 5x2 – 5

= (6x3 – 6x3 ) + (-3x2 – 2x2 + 5x2) – 5

= 0 + 0 – 5

= - 5

2 tháng 4 2023

1)10x-3x(x-5)+3(x2-4x)-3x

<=>3(x2-4x)+10x-3x-3x(x-5)

<=>3(x2-4x)=7x-3x(x-5)

<=>3x2-12x+7x-3x2+15x

<=>3x2-3x2-12x+7x+15x

<=>-12x+7x+15x

<=>10x

2)5y+1-4.5y

<=>51.5y-4.5y

<=>5y(51-4)

<=>5y.1

<=>5y

 

17 tháng 7 2017

a) 3(x-1)-2|x+3| = 3x-3-2(x+3) = 3x-3-2x+6 = (3x-2x)+(6-3)=x+3

b) 2|x-3|-|4x-1| = 2(x-3)-(4x-1) = 2x-6-4x+1 = (2x-4x)-(6-1) = -2x-5

HQ
Hà Quang Minh
Giáo viên
20 tháng 9 2023

a)      Cách 1:

\(6(y - x) - 2(x - y)\)

\( = 6y - 6x - 2x + 2y\)

\( = 8y - 8x\)

Cách 2:

\(6(y - x) - 2(x - y)\\= 6(y-x)+2(y-x)\\=(6+2).(y-x)\\=8.(y-x)\\=8y-8x\)

b)      \(3{x^2} + x - 4x - 5{x^2}\)

\( = (3{x^2} - 5{x^2}) + (x - 4x)\)

\( =  - 2{x^2} - 3x\)